Circulating soluble CD36 as a novel biomarker for progression and prognosis of HBV-related liver diseases - Cai, Chunxian; Xiao, Anhua; Luo, Xiaoqing; Zheng, Enze; Li, Yiyu; Lei, Yu; Zhong, Shan; Chen, Yaxi; Yang, Ping; Tang, Zhurong; Zhou, Zhi (Frontiers in Microbiology, 2022)
Background Our previous study suggested CD36 may be a positive regulator of hepatitis B virus (HBV) replication in vitro. Therefore, the present study aimed to investigate whether circulating soluble CD36 (sCD36) could serve as a diagnostic and prognostic biomarker for HBV-related liver diseases based on the clinic collected data. Methods A total of 282 subjects were divided into healthy controls (HC, n = 47), chronic hepatitis B (CHB, n = 68), HBV-related liver cirrhosis (HBV-LC, n = 167). Soluble CD36 in plasma was measured by ELISA, and monocyte or platelet CD36 expression was determined by flow cytometry. Results There was a step-wise increase of sCD36 with the progression of chronic HBV infection, and it was the highest in the HBV- LC group with liver failure (1.50, IQR:1.04–2.00) as compared with HC (0.38, IQR:0.27–0.38), CHB (0.75, IQR:0.40–1.13), and HBV-LC without liver failure (1.02, IQR,0.61–1.35) group. Circulating sCD36 was not correlated with serum HBV DNA levels, but correlated with liver function parameters. Additionally, ROC analysis confirmed sCD36 could be used to predict liver failure for HBV-LC patients, which yielded an AUC of 0.775 with 71.0% sensitivity and 72.2% specificity. Multivariate logistic regression analysis revealed sCD36 is an independent risk factor in predicting liver failure. Moreover, plasma sCD36 in HBV-LC patients was significantly correlated with prognostic indices, including MELD, MELD-Na and CHILD-PUGH scores. On the other hand, CD36 expression on monocytes or platelets was positively correlated with plasma sCD36 levels, whereas they were not strongly associated with the disease severity. Conclusion Circulating sCD36 could be used as a novel noninvasive biomarker for predicting liver failure and prognosis in chronic HBV infected patients.